Polityczne aspekty rozbrojenia (1919—1925) - Sierpowski, Stanisław (Acta Universitatis Lodziensis. Folia Historica, 1983)
From among: different points of viewing the disarmament problem, the political sphere seems to offer the most useful historical perspective. Without neglecting and diminishing other determinants of disarmament including social, economic, and finally military (technical) in its strict sense, I believe that disarmement treated as a unique synthesis of international relations should rank first. Moreover, with regard to disarmament better than in other fields of collective life, there can be seen relativism of evaluations which are so expressively formulated taking into account one's own i.e. national point of view. Whenever a representative of any state was speaking about disarmament he had in his mind first of all potential enemies and expected their disarmament. On the other hand, whenever security was an object al negotiations, the attitude of delegates of particular states was undergoing a fundamental change. Protection of „one's own home" was the first and most often their only task.